Strategi Pemasaran Hijau Berbasis Kearifan Lokal untuk Meningkatkan Daya Saing UMKM Ramah Lingkungan di Sulawesi Utara - Kumaat, Arief Perdana; Supit, Vekky; Paendong, Melky Krisna Elia; Kaparang, Gratia Natrina (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2025)
This study aims to analyze green marketing strategies to strengthen the competitiveness of environmentally friendly MSMEs in North Sulawesi through the MAPALUS (Mari Pakai Lokal Unggulan Sulut) program. The initiative is inspired by the Minahasa cultural value of mutual cooperation (gotong-royong/mapalus), which has been adapted as a pentahelix-based collaboration model involving academia, government, industry, communities, and media to facilitate the dissemination and downstreaming of local innovations. A qualitative case study approach was applied, focusing on the series of activities under MAPALUS Expo, MAPALUS Talk, and MAPALUS Stories. The findings reveal that integrating the MAPALUS concept with the green marketing mix (product, price, place, promotion, and people) significantly strengthens the local innovation ecosystem. Environmentally friendly MSME products gained wider exposure through exhibitions and media coverage, while sustainability-oriented promotional strategies enhanced consumer trust. Furthermore, multiparty collaboration expanded distribution access and created business partnership opportunities that support the downstreaming of vocational research outputs. These results underscore that combining local wisdom and green marketing not only fosters literacy and adoption of appropriate technologies but also acts as a catalyst for building sustainable MSME competitiveness in North Sulawesi.